EVALUATING COMPUTER LITERACY AMONG TEACHERS IN PUBLIC PRIMARY SCHOOLS IN RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Developing the educational ecosystem in Nigeria entails adopting the growing educational technology relevant to today’s learning. Computer literacy has various potential benefits to the deployment of edutech in learning, and these benefits are manifest in educational delivery. The present study measures the computer literacy levels of primary school teachers in River State, Nigeria. A convenience sample of fifty-one primary school teachers was drawn from primary schools in Omoku, River State. The respondents, comprising males and females aged 25 to 65, completed a self-report measure of the computer literacy scale. The result demonstrated that most participants scored low on the literacy scale (57.75%). On the other hand, 31.25% of the participants scored high on the CLS. The finding has implications for developing education in River State, Nigeria.